Analysis of the Implementation of Risk-Mitigation Governance in Public Services Near Yogyakarta International Airport - Idham Ibty; Subando Agus Margono; Erwan Agus Purwanto (Indonesian Association for Public Administration, 2023)
The public service risk mitigation implemented by local governments in Indonesia in tackling potential risks and the impact of development on local areas is important for governance reform. This study aims to analyze the public service risk mitigation carried out by the Government of Kulon Progo Regency in the YIA area. This study is a type of qualitative research with an instrumental case study methodology. Data were collected by analyzing secondary data, as well as primary data through interviews and observations. The analysis was carried out using triangulation techniques, policy adoption, comparison, searching for data explanations and inductive reasoning, and FGDs. The study findings show that risk-mitigation governance can shape public service providers to face potential risks due to reducing negative impacts on citizens’ basic rights and inequalities in the community. The risk-mitigation governance implementation runs led by the commitment of risk-oriented-local leaders, harmonization of regulations has not integrated to local-sector- law, stakeholder involvement with engagement the participation of basic service users, the private sector, as well as university, community representatives, media, and NGOs, with a collaborative and adaptable approach. Compliance and synergy among stakeholders are the most important factors forming public service risk mitigation.